Perubahan Distribusi Populasi Dari Schismatoglottis lancifolia Hall. et Englar di Hutan Bukit Pinang-pinang - - Khairinnisa; Erizal Mukhtar; - Chairul (Jurnal Biologi Universitas Andalas, 2014)
An investigation on the changes of individual number and distribution pattern of Schismatoglottis lancifolia Hall. et Englar at permanent forest plots in Bukit Pinang-Pinang has been carried out from September 2012 to December 2012. The results showed that populations of Schismatoglottis lancifolia was 51.63% decreased when compared to the previous observations in 1985. The distribution pattern of the species was clumped (Morishita Index : 3.2) that was similar pattern reported in 1985. Distribution pattern was influenced by relative light intensity due to topography variations. Keywords: Bukit Pinang-pinang, distribution population, Schismatoglottis lancifolia.